Challenges and Opportunities in Urban Waste and Water Management in Assam: A Guwahati Perspective - Diksha Dutta; Kasturi Borah (International Journal of Environmental Planning and Development Architecture, 2026)
Water and waste management problems are becoming more urgent in rapidly urbanizing areas like Guwahati, Assam. Current household practices, public awareness, and infrastructure support that either facilitate or impede waste and water management were evaluated in this case study. A structured online survey was used to gather data from fifty-five respondents in Guwahati, primarily urban youth, using a mixed-methods technique. Although low levels of waste generation were reported, the results show that poor waste disposal techniques and a widespread practice of not separating waste at the household level exist, with little infrastructure and awareness-raising resources to support them. In regard to water management, encouraging findings included the use of dual-flush toilets; however, the uptake of greywater reuse and rainwater harvesting was minimal. It was also noted that the vast majority of participants indicated little or no awareness of the government's current initiatives, which indicates a fundamental gap in communication about government services. This study highlights significant gaps in outreach, municipal services, and incentives for sustainable household practices, which need to be addressed. Overall, this study provides a good baseline for policy development and environmental planning in relation to environmental justice in Assam and more widely for urban ecosystems.
Keywords: Guwahati; Waste management; climate resilience; rainwater harvesting; solid waste disposal; urban infrastructure; urban sustainability; waste segregation; water conservation